Long term assessment of antibiotic prophylaxis and biliary microbiome in pancreaticoduodenectomy. Issue 11 (November 2022) - Said, Sayf A.; Hossain, Mir S.; DeMare, Alexander; Perlmutter, Breanna C.; McMichael, John; Joyce, Daniel; Simon, Robert; Augustin, Toms; Walsh, R.M.
Abstract: Introduction: Surgical site infections (SSI) can represent a major complication of pancreaticoduodenectomy (PD). We summarize the outcomes of process improvement efforts to reduce the SSI rates in PD that includes replacing Cefazolin with Ceftriaxone-Metronidazole as antibiotic prophylaxis. Additional efforts included current assessment of biliary microbiome and potential prophylactic failures based on bile cultures and suspected antibiotic allergies. Method: A single-center review of PD patients from January-2012 to March-2021. Study groups were divided into Pre and Post May-2015 (Group 1 and 2, respectively) when Ceftriaxone-Metronidazole prophylaxis and routine intraoperative cultures were standardized. Univariate and multivariable analyses were conducted to assess groups' differences and association with SSI. Results: Six hundred ninety patients identified [267(38.7%) and 423(61.3%) in Group 1 and Group2, respectively]. After antibiotic change, SSI rates decreased from 28.1% to 16.5% (incisional: 17.6%–7.5%, organ-space or abscess: 17.2%–13.0%), Group 1 and Group 2, respectively, P<0.001. Ceftriaxone-Metronidazole was used in 75.9% of patients Group 2. When adjusting for other covariates, an SSI-decrease was associated only with Ceftriaxone-Metronidazole (OR 0.34, P<0.001). Conclusions: Ongoing process improvement has resulted in decreased SSIs with Ceftriaxone-Metronidazole prophylaxis. The benefit of Ceftriaxone-Metronidazole is independent of the biliary microbiome. Improving prophylaxis for those with suspected penicillin allergy is warranted.